Satisfaction level of Employees regarding HR Practices in Sugar Industry - Gupta, Dipika (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
India is the largest consumer & second largest producer of sugar in the world. The Indian sugar industry is the second large agro industry Located in the rural India. The Indian sugar has a turnover of Rs.500 billion per annum & it contributes almost Rs.22.5 billion to the central & state as tax, and excise duty every year. It is the second largest agro-processing industry in the country after cotton textiles. The sugar industry in the country uses only sugarcane as input; hence Sugar Company’s have been established in large sugarcane growing states like Uttar Pradesh, Maharashtra, Karnataka, Gujarat, and Tamil Nadu & Andhra Pradesh. Method of collecting primary data was through questionnaire and personnel interview and secondary data has been collected through Internet, observation, company manual etc. For the purpose of study employees of the RANNA Sugar Company have been chosen as a sample size of 100 through convenient random sampling. Data collected was tabulated and interpretated by using SPSS software to derive conclusion. Medical facility provided to the employees is highly satisfied as management is highly concerned about the employees and their health The relationship between the management and employees is good.61% of employees say they are satisfied with the way their grievances are addressed. Transportation facility provided by the company is not up to the mark, because 35% respondents are strongly dissatisfied. Keywords: Medical facility, sugar industry, Transportation facility